Handwritten Digits OCR for Identifying Examinee Number on Objective Test Answer Sheet / การรู้จำตัวเลขอารบิกจากลายมือสำหรับระบุรหัสผู้สอบบนกระดาษคาตอบแบบปรนัย - Sattayakawee, Nutchanat; Ratchapaiboon, Teeradetch; Jetpipattanapong, Duangpen (Naresuan University Journal: Science and Technology (NUJST); Vol 22 No 2 (2014): May-August 2014, 2014)
บทความนี้นาเสนอการรู้จาตัวเลขจากลายมือโดยการประมวลผลภาพ ซึ่งมีเป้าหมายเพื่อนาไปใช้ในการระบุเลขประจาตัวผู้สอบในกระดาษคาตอบของข้อสอบแบบปรนัย โดยใช้ภาพจากเครื่องสแกน ซึ่งรหัสประจาตัวผู้สอบจะต้องเขียนเป็นตัวเลขอารบิกด้วยปากกาลูกลื่นสีน้าเงินไว้ที่มุมบนซ้ายของกระดาษคาตอบ หลักการที่ใช้ในการรู้จาตัวเลข คือ เทคนิคโปรเจคชั่นในแนวแกน 4 แกนได้แก่ แนวนอน (Horizontal) แนวตั้ง (Vertical) แนวทแยงซ้าย (Left Diagonal)และแนวทแยงขวา (Right Diagonal) และนาวิธีทางสถิติอย่างง่ายมาช่วยวิเคราะห์คาตอบ จากการทดสอบความถูกต้องของการทางานโดยตรวจสอบตัวเลขอารบิกจานวน 600 ตัว โดยมี เลขอารบิก 0 - 9 อย่างละ 60 ตัว พบว่า ระบบสามารถแยกตัวเลขได้ถูกต้อง 465 ตัว คิดเป็นร้อยละ 77.50 คำสำคัญ: การรู้จำตัวเลข ลายมือ โปรเจคชั่น ฮีสโตแกรม การรู้จำอักขระทางภาพ This paper presents the recognition of handwritten digits using image processing. It aims at identifying identification numbers of examinees on multiple choice answer sheets. Input images are from a scanner. In addition, an identification number must be written in Arabic numerals with a blue ballpoint pen on the upper left corner of an answer sheet. The proposed technique is based on projection profiles of 4 axes: horizontal, vertical, left diagonal and right diagonal axes. Simple statistical analysis is then applied in order to recognize the characters. With the test samples of 600 digits, each of which was represented by 60 samples, the test result showed that the algorithm recognized 465 digits correctly, giving the accuracy rate of 77.50 %. Keywords: Digit Recognition, Handwritten, Projection, Histogram, Optical Character Recognition
Keywords: การรู้จำตัวเลข ลายมือ โปรเจคชั่น ฮีสโตแกรม การรู้จำอักขระทางภาพ Digit Recognition, Handwritten, Projection, Histogram, Optical Character Recognition